Honouring His Royal Highness the Crown Prince of Bhutan: Megalestes gyalsey (Odonata: Synlestidae) - Gyeltshen, T.; Kalkman, V.j.; Orr, A.g. (Zootaxa, 2017)
Megalestes gyalsey spec. nov. is described from a single male from Trongsa District in Bhutan. The species was discovered during field work conducted in 2015 for the Bhutan invertebrate biodiversity project. The species is named in honour of His Royal Highness Crown Prince Jigme Namgyel Wangchuck, the Gyalsey of Bhutan, on the occasion of his first birthday.